Headspace Solid Phase Microextraction Application for Pesticide Residues in Fruits and Vegetables - Frage, Abookleesh; Almrhag, Omar; Zatout, Massoud (Arab Journal for Sciences and Research Publishing, 2016)
Headspace solid phase microextraction, fundamental& principle with its application on the determination of various pesticides are reviewed in this article. Pesticides extraction as a sample preparation step prior to subsequent analysis is aimed to achieve a reliable and accurate determination of this contaminants residue in food. Fast and high efficiency extraction process with free solvent consumption and overall cost is achieved through headspace solid phase micro extraction. HSPME is an equilibrium process which depends on the physio-chemical properties of the analyte to be extracted. Sample preparation and extraction condition such as fiber coating, temperature, time etc, have a direct impact on the extraction efficiency and sensitivity of headspace technique.
Keywords: Pesticides; vegetables; Fruit; Headspace Solid Phase Microextraction